The Effect of a Folic Acid Supplementation Program During the Preconception Period on Reducing the Risk of Neural Tube Defects in Pregnancy - Hanifah, Astin Nur; Nurhaedah, Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background:Neural tube defects (NTDs) are serious congenital abnormalities of the brain and spinal cord that develop in the first 28 days after conception. One of the main risk factors is folic acid deficiency in early pregnancy. Folic acid supplementation before conception has been shown to significantly reduce the risk of NTDs. Objective:To determine the effect of folic acid supplementation program during preconception period on reducing the risk of NTDs in pregnancy. Method:This study used a prospective cohort design in 240 women of childbearing age (WUS) who were planning a pregnancy in the working area of Community Health Center X. The intervention group (n=120) received 400 μg/day of folic acid supplementation at least 3 months before conception, while the control group (n=120) did not receive routine supplementation. NTDs incidence data were obtained from ultrasonography (USG) examinations and medical records up to 20 weeks of gestation. Data analysis used the relative risk (RR) test with 95% CI. Results:The incidence of NTDs in the intervention group was 0.83% (1/120), while in the control group it was 6.67% (8/120). The analysis showed a RR of 0.12 (95% CI: 0.02–0.95; p=0.044), meaning that preconception folic acid supplementation reduced the risk of NTDs by 88%. Conclusion:Preconception folic acid supplementation programs are effective in reducing the risk of NTDs. Routine folate supplementation programs are recommended for women planning pregnancy.